1999
DOI: 10.1002/(sici)1096-8628(19990402)83:4<268::aid-ajmg7>3.0.co;2-k
|View full text |Cite
|
Sign up to set email alerts
|

Electrodermal responses to sensory stimuli in individuals with fragile X syndrome: A preliminary report

Abstract: The fragile X mutation and fragile X syndrome are associated with hyperarousal, hyperactivity, aggression, and anxiety. These may be related to strong reactions to auditory, tactile, visual, and olfactory stimuli [Hagerman, 1996b; Hagerman and Cronister, 1996]. However, almost no data exist describing hyperarousal and sensory sensitivity in individuals with the fragile X mutation. This study establishes a reliable laboratory paradigm for examining reactions to sensory stimuli. We found the pattern of electrode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
256
1
3

Year Published

1999
1999
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 361 publications
(273 citation statements)
references
References 35 publications
13
256
1
3
Order By: Relevance
“…This scale was developed by adapting procedures from sensory processing assessments for children (Baranek & Berkson, 1994;Miller et al, 1999).…”
Section: Methods Subjectsmentioning
confidence: 99%
See 1 more Smart Citation
“…This scale was developed by adapting procedures from sensory processing assessments for children (Baranek & Berkson, 1994;Miller et al, 1999).…”
Section: Methods Subjectsmentioning
confidence: 99%
“…NIH-PA Author Manuscript NIH-PA Author Manuscript estimated to occur in 5% of the general population (Ahn, Miller, Milberger, & McIntosh, 2004) and seem to pose a unique challenge for people with developmental disabilities (Baranek, 2002), including autism, attention deficit hyperactivity disorder (ADHD), fragile X syndrome, and other developmental disabilities (Ayres & Tickle, 1980;Baranek, 1999;Baranek & Berkson, 1994;Baranek, Foster, & Berkson, 1997;Cermak & Daunhauer, 1997;Grandin, 1992;Kinnealey, 1973;Larson, 1982;Mangeot et al, 2001;Miller et al, 1999). Understanding the neurobiological processes associated with sensory processing disruptions is important to developing appropriate preventative and intervention approaches.…”
Section: Nih-pa Author Manuscriptmentioning
confidence: 99%
“…One of the most common clinical features of FXS is heightened sensitivity to sensory stimulation (Frankland et al, 2004;Miller et al, 1999). PPI is a widely used model to study basic sensorimotor processing and has shown to be related to mGluR signaling (Grauer and Marquis, 1999).…”
Section: Mpep Rescues Prepulse Inhibition Of Startle Defect In Fmr1 Kmentioning
confidence: 99%
“…Anxiety is commonly featured with memory deficits in FX individuals Tsiouris and Brown 2004). Although anxiety is difficult to detect in individuals with intellectual disability, behavioral equivalents of anxiety have been reported in FX (Sullivan, Hooper et al 2007) and are likely related to the hypersensitivity and hyperarousal (Cohen 1995) described in electrodermal studies of FX individuals (Miller, McIntosh et al 1999). As Hagerman notes , pharmacologic inhibition of the cAMP second messenger system prevents normal sensitization to sensory stimuli in Aplysia (Kandel and Schwartz 1982) which has direct implications for the abnormal sensitization seen in FX individuals.…”
Section: Fragile X Patientsmentioning
confidence: 99%